Foundations of indigenous knowledge on disasters due to natural hazards: lessons from the outlook on floods among the Bayira of the Rwenzori region. Issue 1 (3rd October 2022) - Bwambale, Bosco; Muhumuza, Moses; Kahigwa, Thaddeo Tibasiima; Baluku, Stanley Mbalibulha Bakahinga; Kasozi, Humphrey; Nyeko, Martine; Kervyn, Matthieu
Abstract : The role of indigenous knowledge in increasing context specificity and exposing blind spots in scientific understanding is widely evidenced in disaster studies. This paper aims to structure the processes that shape indigenous knowledge production and its optimisation using the case of floods. An inductive analytical approach is applied among riparian indigenous communities (focus on the Bayira) of the Rwenzori region of Uganda where plenty of indigenous flood practices have been recorded. Indigenous knowledge of floods is found to be based on intimate comprehension of local hydrometeorological regularities. Insofar as these regularities follow natural dynamics, indigenous socio‐epistemic processes are noted to be consistent with the laws of nature. Coupled with regular open sociocultural deliberations, the conceptualisation of hydrometeorological regularities induces an indigenous ontology and empiricist epistemology. This, together with the techniques used, is the driver of crucial epistemic virtues which enable indigenous knowledge to provide disaster solutions that are adapted, pragmatic, and holistic. نبذة مختصرة: يتضح الدور الذي تلعبه المعرفة الأصلية أو التقليدية في زيادة خصوصية السياق وكذلك الكشف عن النقاط العمياء في الفهم العلمي على نطاق واسع في مجال دراسات مخاطر الكوارث. كمساهمة في تعزيز هذا الدليل، تهدف هذه الدراسة إلى هيكلة العمليات التي تشكل إنتاج المعرفة الأصلية وتحسينها بناءً على حالة الفيضانات. تم استخدام نهج استنتاجي تحليلي للتحقيق في مظاهر معرفة السكان الأصليين وتنظيم عملياتهم الاجتماعية المعرفية. يتم تطبيق هذا النهج بين مجتمعات السكان الأصليين ل باييرا(التركيز على باييرا) في منطقة روين زوري حيث يتم تسجيل الكثير من ممارسات السكان الأصليين بشأن الفيضانات. تظهر النتائج أن معرفة السكان الأصليين بالفيضانات تستند إلى فهم وثيق لانتظام الأرصاد الجوية المائية المحلية. وبقدر ما تتبع هذه التنظيمات المحلية الديناميكيات الطبيعية، يُلاحظ أن العمليات الاجتماعية المعرفية الأصلية تتبع ضمنيًا قوانين الطبيعة. بالاقتران مع المداولات الاجتماعية الثقافية المنتظمة المفتوحة، فإن وضع تصور لانتظامات الأرصاد الجوية المائية المحلية يستحث نهجًا تجريبيًا وجوديًا أصليًا. هذا النهج جنبًا إلى جنب مع التقنيات المستخدمة هو المحرك للفضائل المعرفية الحاسمة مثل الاستناد إلى النتائج الملموسة والتفكير المنهجي. هذه الفضائل هي التي تمكن المعرفة الأصلية من توفير حلول محلية متكيفة وعملية وشاملة للكوارث مثل الفيضانات. الكلمات الدالة: الفلسفة العرقية، الطريقة الأصلية، العلوم الأصلية، المخاطر الطبيعية، الطبيعة الاجتماعية 摘要: 在灾害风险研究领域，越来越多的证据表明，土著知识有助于增加背景特异性以及揭示科学理解盲点。本研究的目的是根据洪水案例，构建土著知识产生和优化的过程，进一步丰富相关证据。本文采用归纳分析方法，调查土著知识表现形式和社会认知过程的构建。这种方法应用在鲁文佐里地区的河岸原住民社区（主要是巴伊拉人），那里许多土著人对洪水的做法得到了记录。结果表明，关于洪水的土著知识是基于对当地水文气象规律的深入了解。由于这些地方性的规律在某种程度上遵循着自然的动态变化，因此土著社会认知过程是遵循自然规律的。再加上定期的公开社会文化审议，当地水文气象规律的概念化引发了本土本体论和经验主义方法。这种方法结合所使用的技术，构成了关键美德认知论的驱动力，美德认知论是基于可靠结果和系统思维。正是这些美德使土著知识能够提供适合、务实和全面的当地解决方案，以应对洪水等灾害。 关键词：民族哲学，土著方法，本土科学，自然灾害，社会科学